Biomaterial scaffolds for non-invasive focal hyperthermia as a potential tool to ablate metastatic cancer cells. (June 2018) - Pelaez, Francisco; Manuchehrabadi, Navid; Roy, Priyatanu; Natesan, Harishankar; Wang, Yiru; Racila, Emilian; Fong, Heather; Zeng, Kevin; Silbaugh, Abby M.; Bischof, John C.; Azarin, Samira M.
Abstract: Currently, there are very few therapeutic options for treatment of metastatic disease, as it often remains undetected until the burden of disease is too high. Microporous poly(ε-caprolactone) biomaterials have been shown to attract metastasizing breast cancer cells in vivo early in tumor progression. In order to enhance the therapeutic potential of these scaffolds, they were modified such that infiltrating cells could be eliminated with non-invasive focal hyperthermia. Metal disks were incorporated into poly(ε-caprolactone) scaffolds to generate heat through electromagnetic induction by an oscillating magnetic field within a radiofrequency coil. Heat generation was modulated by varying the size of the metal disk, the strength of the magnetic field (at a fixed frequency), or the type of metal. When implanted subcutaneously in mice, the modified scaffolds were biocompatible and became properly integrated with the host tissue. Optimal parameters for in vivo heating were identified through a combination of computational modeling and ex vivo characterization to both predict and verify heat transfer dynamics and cell death kinetics during inductive heating. In vivo inductive heating of implanted, tissue-laden composite scaffolds led to tissue necrosis as seen by histological analysis. The ability to thermally ablate captured cells non-invasively using biomaterial scaffolds has the potential to extend the application of focal thermal therapies to disseminated cancers. Graphical abstract: